Mestrado Profissional em Educação - Formação de Formadores (PUC-SP): contribuições para coordenadores pedagógicos da Rede Municipal de Ensino de São Paulo - Pacitti, Monie Fernandes (2018)
One of the alternatives found by pedagogical coordinators to improve the performance of their duties has been to return to university. The Professional Master's in Education: Training of Formators of the Pontifícia Universidade Católica de São Paulo - PUCSP (Formep) has welcomed these professionals who seek theoretical and practical support for the development of their varied attributions, in order to contribute to their professional development. It was based on the assumption that the understanding and challenges of the practice would be contemplated by the moments of theoretical deepening, exchanges of experience and learning of the research of the professional practice of these pedagogical coordinators. The general objective of the research was to investigate the contributions of Formep to the professional development of the pedagogical coordinators of the Municipal Education Network of the city of São Paulo. It was adopted as theoretical reference Marcelo (2009), Vaillantt and Gaibisso (2016), Libâneo (2015), Placco and Almeida (2011, 2012), André (2016). The research was based on the qualitative approach, with data collected through semi-structured interviews with five pedagogical coordinators of this municipal school system and who studied the first three classes of Formep (2013, 2014 and 2015) and analysis of pedagogical documents concerning the creation and regulation of Formep and a municipal law decree that deals with the attributions of these coordinators. The method for data analysis followed the assumptions of Prose Analysis (ANDRÉ, 1983). The results show that the Professional Masters contributed to the professional development of the pedagogical coordinators, since the main challenges faced by them, the teacher training in the school and the interpersonal relations, were object of reflection and analysis about the role of these coordinators, which led to changes in the Special Action Project (PEA) and the transformation of interpersonal relationships, as well as to active listening and appreciation of teachers. In addition, the research carried out allowed a more critical and reflexive look at the practice and it was given a new meaning, thus resulting in a more investigative attitude towards the work developed in schools by these pedagogical coordinators